A spectrophotometric method for the determination of lisinopril in tablet formulation - Çetin, G; Sungur, S (FREUND PUBLISHING HOUSE LTD, 2006)
A simple and sensitive spectrophotometric method is presented for the assay of lisinopril in tablets. The method involves the formation of hydroxamate by the reaction of carboxyl group with hydroxylamine hydrochloride (HAHC) and dicyclohexylcarbodiimide (DCC) and the formation of the reddish brown coloured iron(Ill) hydroxamate complex with iron (III) perchlorate in ethanolic solution of perchloric acid. The formation of hydroxamate was completed in 10 min. at 40 degrees C with 0.5 ml of 0.3 mol L-1 ethanolic hydroxylamine hydrochloride and 0.5 ml of 0.3 mol L-1 ethanolic DCC solutions for lisinopril. 1.0 ml of 0.02 mol L-1 iron (III) perchlorate in 0.2 mol L-1 ethanolic perchloric acid solution were required for complex formation. The complex has shown maximum absorbance at 506 nm. The quantification limit is 2.759 x 10-5 mol L-1 (11. 174 mu g mL(-1)) at 506 nm. The limit of detection is 1.403 x 10(-6) mol L-1 (0.568 mu g mL(-1)) at 506 nm. The method was applied to commercially available tablets and the results were statistically compared with those obtained by an UV spectrophotometric method using t- and F- tests at 95 % confidence level.
Keywords: lisinopril determination; dicyclohexylcarbodiimide; hydroxylamine hydrochloride; iron(III) hydroxamate complex; spectrophotometry; ANGIOTENSIN-CONVERTING ENZYME; PERFORMANCE LIQUID-CHROMATOGRAPHY; PHARMACEUTICAL DOSAGE FORMS; INHIBITOR LISINOPRIL; ACE-INHIBITORS; HYDROCHLOROTHIAZIDE; ENALAPRILAT; DRUGS; ASSAY; Chemistry